2003
DOI: 10.1073/pnas.1533177100
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric recombinases with designed DNA sequence recognition

Abstract: Site-specific recombination typically occurs only between DNA sequences that have co-evolved with a natural recombinase enzyme to optimize sequence recognition, catalytic efficiency, and regulation. Here, we show that the sequence recognition and the catalysis functions of a recombinase can be specified by unrelated protein domains. We describe chimeric recombinases with a catalytic domain from an activated multiple mutant of the bacterial enzyme Tn3 resolvase, fused to a DNA recognition domain from the mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
107
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 24 publications
1
107
0
1
Order By: Relevance
“…Exciting data are appearing from labs exploring the use of rare-cutting endonucleases such as I-SceI and zinc-finger/FokI chimeras that can cleave genomic DNA at fixed (and Targeted gene repair: progress and prospects H Parekh-Olmedo et al few) locations. [15][16][17][18][19] It is possible that by minimizing the number of DSBs, the gene repair frequency will be elevated without the concurrent pleiotropic effects. The events of the second phase where the 'correction' of the targeted mutant gene actually occurs are poorly understood.…”
Section: Prospectsmentioning
confidence: 99%
“…Exciting data are appearing from labs exploring the use of rare-cutting endonucleases such as I-SceI and zinc-finger/FokI chimeras that can cleave genomic DNA at fixed (and Targeted gene repair: progress and prospects H Parekh-Olmedo et al few) locations. [15][16][17][18][19] It is possible that by minimizing the number of DSBs, the gene repair frequency will be elevated without the concurrent pleiotropic effects. The events of the second phase where the 'correction' of the targeted mutant gene actually occurs are poorly understood.…”
Section: Prospectsmentioning
confidence: 99%
“…Synthetic zinc finger DNA-binding proteins have been generated for many sequences, using several approaches (15-17). Capitalizing on this work, researchers have incorporated synthetic zinc finger proteins into a wide variety of molecular tools (7, 18-29).The DBD of a hyperactive serine recombinase can be replaced with a zinc finger protein of higher affinity and specificity (7,25). This substitution retargets recombination to sequences flanked by zinc finger binding sites (ZFBS) (Fig.…”
mentioning
confidence: 99%
“…Synthetic zinc finger DNA-binding proteins have been generated for many sequences, using several approaches (15)(16)(17). Capitalizing on this work, researchers have incorporated synthetic zinc finger proteins into a wide variety of molecular tools (7,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First and foremost are the development of new tools capable of introducing genomic modifications in the absence of DNA breaks. Targeted recombinases (Akopian et al 2003;Mercer et al 2012), which can be programmed to recognize specific DNA sequences (Gaj et al 2013;Sirk et al 2014;Wallen et al 2015) and even integrate therapeutic factors into the human genome (Gaj et al 2014b), are one such option. More recent work has indicated that single-base editing without DNA breaks can be achieved using an engineered Cas9 nickase complex (Komor et al 2016), although it remains unknown how effective this technology is in therapeutically relevant settings.…”
Section: Discussionmentioning
confidence: 99%